2014
DOI: 10.1016/j.jacc.2014.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Individual Platelet Reactivity Over Time in Patients Treated With Clopidogrel

Abstract: Measurements of platelet reactivity vary over time in a significant proportion of patients. Thus, treatment adjustment according to platelet function testing at a single time point might not be sufficient for guiding antiplatelet therapy in clinical or research settings. (Escalating Clopidogrel by Involving a Genetic Strategy-Thrombolysis In Myocardial Infarction 56 [ELEVATE-TIMI 56]; NCT01235351).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 30 publications
6
58
3
2
Order By: Relevance
“…Other studies have demonstrated changes in platelet reactivity over time, mainly between 1 and 3 months after the index event. 7,8, 13 In line with those results, our study showed that, for both clopidogrel and prasugrel, the platelet reactivity varies significantly between discharge and 3 months, being more stable between 3 and 6 months. Moreover, the proportion of patients showing HPR status over time was higher using clopidogrel than prasugrel, likely as a reflection of the more constant effect of the novel thienopyridine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies have demonstrated changes in platelet reactivity over time, mainly between 1 and 3 months after the index event. 7,8, 13 In line with those results, our study showed that, for both clopidogrel and prasugrel, the platelet reactivity varies significantly between discharge and 3 months, being more stable between 3 and 6 months. Moreover, the proportion of patients showing HPR status over time was higher using clopidogrel than prasugrel, likely as a reflection of the more constant effect of the novel thienopyridine.…”
Section: Discussionsupporting
confidence: 89%
“…This intra-individual variation was observed in the ELEVATE TIMI-56 trial in which approximately 11-15% of patients had a change in their responder status when tested at 2 different time points (each 14 days), even with higher clopidogrel doses. 13 Data coming from the Assessment of Dual AntiPlatelet Therapy With Drug-Eluting Stents (ADAPT-DES) study suggest a considerable variation in the individual on-clopidogrel platelet reactivity, which was present in both the acute and subacute phases. 14 In addition, the platelet inhibition following the clopidogrel loading dose is higher during the early phase than in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These results are concordant with those of a recent study reporting variable responses to clopidogrel among patients with coronary artery disease. 11 In healthy subjects, the mean and median VerifyNow values did not significantly differ when participants were tested 20 to 24 hours after the final dose of 80 mg to 325 mg of aspirin. 14 However, in contrast to healthy volunteers, patient populations at risk for arterial thrombosis have pathophysiologies that evoke variable intensities and mechanisms to stimulate platelets.…”
Section: Discussionmentioning
confidence: 84%
“…51,52 Furthermore, measurements of platelet reactivity vary over time in a significant proportion of patients. 53 Thus, treatment adjustment according to platelet function testing at a single time point might not be sufficient for guiding antiplatelet therapy. In contrast, monitoring the effect of clopidogrel therapy by CYP2C19 genotyping (as discussed in the following sections) does not vary over time.…”
Section: Casementioning
confidence: 99%